Large-Element-Spacing Array Design Algorithm for Rotated Subarray via Alternating Iterative Convex Optimization - Yang, Gongqing; Xu, Zhenhai; Dong, Wei; Zeng, Hui; Li, Xinxin (IEEE transactions on antennas and propagation, 2025)
This paper introduces a novel optimization method for designing rotated subarrays. Rotated subarrays typically employ modular configurations with large element spacing to enable cost-efficient phased array implementations. The main challenge is reducing grating lobes caused by the large spacing, which is a complex optimization problem. By carefully redesigning the optimization model, this non-convex problem is transformed into a convex form that can be solved efficiently. Numerical results demonstrate superior grating lobe suppression compared to existing methods, while full-wave electromagnetic simulations validate the approach.